Implementasi Program Merdeka Belajar Kampus Merdeka: Perpustakaan yang Efisien dan Aman Berbasis Teknologi Informasi - Fahruraji Fahruraji (THE LIGHT : Journal of Librarianship and Information Science, 2022)
Information technology is one of the factors that affect the success of a program. Information technology can be used as a potential tool that can support the Merdeka Learning Program for the Independent Campus, considering that library access is very necessary to information sources that are multidisciplinary subjects, multiformat, integrated search, local, national and international collections as well as advanced services needed by its users, especially students who study outside their campus through the stages of socialization, education and evaluation to achieve the success of Merdeka Learning Merdeka Campus. The research used in this research is qualitative. Research conducted on natural objects. A natural object is an object that develops as it is, is not manipulated by the researcher and the presence of the researcher does not affect the dynamics on the object. In qualitative research the instrument is a person or human instrument, that is, the researcher himself. To gain a broader and deeper understanding of the social situation under study.